PERAN PERHUTANI DALAM PENYELESAIAN KONFLIK TENURIAL PADA KAWASAN HUTAN: Studi Kasus RPH Ringinpitu BKPH Tanggung KPH Semarang - Ambarwati, Maria Endah; Sasongko, Gatot; Therik, Wilson M.A. (Universitas Kristen Satya Wacana, 2019)
The aim of this research is to describe the role of Perum Perhutani in tenurial conflict resolution in the forest area of Perum Perhutani Kesatuan Pemangkuan Hutan (KPH) Semarang, especially in Resort Pemangkuan Hutan Ringinpitu Bagian Kesatuan Pemangkuan Hutan (BKPH) Tanggung using descriptive methods with in-depth interview, observation and documentation. The informants are the inhabitants of the Ringinpitu village Tanggungharjo District Grobogan Residence and officers from Perum Perhutani. Data analysis technique used is qualitative data analysis. Perum Perhutani has implemented Collaborative Forest Management (PHBM) as a strategy for tenurial conflict resolution and can be classified as problem solving strategy and conflict resolution alternative. Dynamics of the approach used in conflict resolution in RPH Ringinpitu start with a legal approach as well as public consultation, mediation and negotiation. RPH Ringinpitu uses three of four kinds of conflict resolution alternatives which are public consultation, mediation and negoitation.